Breaking Down Silos: Collaborative Care Across Dental, Nursing, Dietetic, Laboratory, and Emergency Services - Asma Yahya Trmah Alrubayyi,; Sukainah Ali Essa Al Sharedah,; Zainab Ahmed Ahmed Alduwani,; Hussain Mohammed Almoosa,; Hussein Abdullah Alessa,; Fwazee Ali Ahmed Alkhames,; Kadhem Mohammed Alkhamis,; Nasser Abdulrahman Abdullah Almuhaydi,; Haydr Abdullah Alsalman,; Mohammed Nasser Al Hashem,; Ali Hussain Al Ali,; Mohammed Kazim Albarry, (International Journal of Medical Toxicology and Legal Medicine, 2024)
In modern healthcare systems, care is often fragmented across different departments and specialties, resulting in inefficient service delivery and suboptimal patient outcomes. Breaking down these silos and fostering interdisciplinary collaboration is essential to improving patient care. This paper explores the importance of collaborative care across key healthcare disciplines—dental care, nursing, dietetics, laboratory services, and emergency services. By integrating these services, healthcare providers can deliver more comprehensive, patient-centered care that addresses the complex needs of individuals. This paper discusses the benefits of collaboration, the challenges in overcoming siloed systems, and provides recommendations for enhancing teamwork and communication across these fields to improve healthcare outcomes.